2016
DOI: 10.1177/0284185115626469
|View full text |Cite
|
Sign up to set email alerts
|

Classification of fatty and dense breast parenchyma: comparison of automatic volumetric density measurement and radiologists’ classification and their inter-observer variation

Abstract: The optimal volumetric threshold of 10% using automatic assessment would classify breast parenchyma as fatty or dense with substantial accuracy and consistency compared to radiologists' BI-RADS categorization, which suffers from high inter-observer variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 20 publications
5
27
0
Order By: Relevance
“…The single radiologist read also poses a potential limitation of this study in that it decreases possible application to other clinics/radiology practices. However, it is reassuring that the findings were consistent with the published studies from Amsterdam and Oslo, 18 , 19 as well as with the unpublished United States–based study of Rafferty et al 21 It remains a conundrum why these 3 studies and our study are at variance with the studies from Turin, New Delhi, and Sydney. 16 , 17 , 20 , 23 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The single radiologist read also poses a potential limitation of this study in that it decreases possible application to other clinics/radiology practices. However, it is reassuring that the findings were consistent with the published studies from Amsterdam and Oslo, 18 , 19 as well as with the unpublished United States–based study of Rafferty et al 21 It remains a conundrum why these 3 studies and our study are at variance with the studies from Turin, New Delhi, and Sydney. 16 , 17 , 20 , 23 …”
Section: Discussionsupporting
confidence: 92%
“…Because Q D increases in half-percent increments, this means that if a patient’s Q D was 13.5% or less, she belonged to the D1-2 category, but if her Q D was 14.0% or more, then she belonged to the D3 category. This finding of a 14% cutoff is similar to the 13.8% cutoff reported by the Amsterdam study 18 and the 10% cutoff reported by the Oslo study, 19 and also similar to the unpublished 13% cutoff attributed by Ciatto et al 20 to the United States–based study of Rafferty et al 21 In contrast, the independent studies done by Ciatto et al 20 and Regini et al 23 in an Italian population reported 22% and 21%, respectively, as the optimal Quantra density cutoff value. Also in contrast were the high Quantra density cutoffs of 19.5% and 20%, respectively, reported by the studies from India and Australia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…No studies have previously examined the three-point scale in relation to estimates of volumetric breast density obtained by the fully automated software. However, several studies have compared fully automated methods for breast density assessment to BI-RADS (85,96,102,103,105,(156)(157)(158)(159)(160)(161)(162), indicating a clear increase in volumetric breast density as the BI-RADS density category increased (103) or a strong relationship between volumetric breast density and the BI-RADS categories (96). Similar trends have been reported in other studies (102,(157)(158)(159)162).…”
Section: Study IVsupporting
confidence: 63%
“…This misclassification could have weakened the agreement between BI-RADS and VDG. A previous study from Norway using the dichotomized BI-RADS density classification (1 and 2 versus 3 and 4) showed that the agreement (measured by kappa with quadratic weights) between reader's median classification and an individual score of five radiologists ranged between 0.76 and 0.93 (176). Thus, even though strong, this agreement is not perfect, and we may therefore have underestimated the agreement between BI-RADS and VDG somewhat in Study IV.…”
Section: Information Biasmentioning
confidence: 74%